2022
DOI: 10.3389/fimmu.2022.915207
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral immune signature resembles tumor microenvironment and predicts clinical outcomes in head and neck squamous cell carcinoma

Abstract: The contour of the tumor immune microenvironment (TIME) is very important for tumor prognostic prediction but hard to be characterized in clinical practice. It is unclear practice whether the peripheral immune signature (pIS) reflects the TIME as a feasible prognostic indicator for head and neck squamous cell carcinoma (HNSCC) patients. Here, we enrolled 599 HNSCC patients from three domestic institutes to explore the relationship between the pIS and survival. The peripheral neutrophil-to-lymphocyte ratio (pNL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Studies have shown that immune cells such as neutrophils and lymphocytes can regulate tumor cell activity by secreting large amounts of cytokines [28]. In addition, high levels of neutrophil-to-lymphocyte ratio (NLR) are thought to be strongly associated with poor tumor outcomes [29,30]. Therefore, neutrophils, lymphocytes and NLR in peripheral blood were included in this study and analyzed for their association with progression after rst-line chemotherapy for TC as well as with PFS.…”
Section: Relationship Of Rs and Combined Radiomics Model To Pfs After...mentioning
confidence: 99%
“…Studies have shown that immune cells such as neutrophils and lymphocytes can regulate tumor cell activity by secreting large amounts of cytokines [28]. In addition, high levels of neutrophil-to-lymphocyte ratio (NLR) are thought to be strongly associated with poor tumor outcomes [29,30]. Therefore, neutrophils, lymphocytes and NLR in peripheral blood were included in this study and analyzed for their association with progression after rst-line chemotherapy for TC as well as with PFS.…”
Section: Relationship Of Rs and Combined Radiomics Model To Pfs After...mentioning
confidence: 99%
“…Prediction by the IRG-Based Signature. For the verification of the IRG-based signature's prognostic performance, the signature's impact on OS in both risk groups was subjected to comparison by Kaplan-Meier (K-M) survival analysis utilizing the "survival" package in R software, followed by the area under the curve (AUC) of the receiver operating characteristic (ROC) curves to assess IRG-based signature's accuracy through the "survival ROC" package in R software [24]. Subsequently, the GEO database (GSE27020) was used for external validation.…”
Section: Prognosismentioning
confidence: 99%